A survey on current knowledge, practice and beliefs related to preoperative antimicrobial decolonization regimens for prevention of surgical site infections among Austrian surgeons. Issue 4 (December 2018) - Tschelaut, L.; Assadian, O.; Strauss, R.; Matiasek, J.; Beer, M.; Angerler, G.; Berger-Grabner, D.; Presterl, E.
Summary: Background: Various measures are considered to reduce the risk of surgical site infection (SSI), including preoperative decolonization. Details of preoperative decolonization practices in surgical departments have not been investigated in Austria. Aim: To analyse the current situation of pre-surgical patient decolonization in national hospitals and to assess the current knowledge on this procedure among surgeons of different surgical disciplines. Methods: A 12-point structured questionnaire was distributed to all Austrian hospitals with at least one surgical department. Findings: Two-thirds (103/158; 65%) of responding surgeons stated that any type of preoperative decolonization is implemented in their surgical department. There was heterogeneity of different protocols, ranging from decolonization of only known S. aureus carriers, of a subgroup of patients, or universal decolonization of all patients before elective surgery. Octenidine was the most frequently used antimicrobial compound (60.2%), followed by mupirocin (38.8%), triclosan (14.6%), polyhexanide (12.6%), chlorhexidine (11.7%), and didecyldimonium chloride (7.8%). Conclusion: Preoperative decolonization seems to be performed in Austrian hospitals on a routine basis. However, this measure is implemented using a variety of modalities, antimicrobial compounds, and staff. Since our survey also demonstrated that those who are better informed about preoperative decolonization are also those who are more convinced of the usefulness of the preventive measure, future activities should not only focus on generating more comparable studies in this field, but should also include targeted education.